Alignment of the Arabic Language Curriculum in Madrasah Aliyah with 21st Century Competency Needs: A Qualitative Study on Graduate Profiles - Fajar Nugraha; Ima ‘Ismatul Hasanah; Rizki Ramadhan (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to examine the extent to which the Arabic language curriculum in Madrasah Aliyah incorporates 21st-century competencies, how its implementation in learning supports the formation of 21st-century graduate profiles, teachers’ and students’ perceptions of the curriculum’s relevance to 21st-century competency needs, and the factors influencing the alignment (or misalignment) of the curriculum with the demands of 21st-century graduate profiles. The research employs a descriptive qualitative approach, with primary data collected from teachers, students, and curriculum coordinators, and secondary data sourced from curriculum documents. Data were gathered through interviews, observations, and documentation. Analysis was conducted using the Miles and Huberman model through stages of data reduction, presentation, and conclusion drawing to provide a valid and comprehensive depiction of the alignment of the Madrasah Aliyah Arabic curriculum with 21st-century competencies. The findings indicate that the Arabic curriculum at Madrasah Aliyah directs learning toward 21st-century competencies; however, its implementation is not yet optimal. Communication competency is the most developed, followed by collaboration through group work. Critical thinking is present implicitly, while creativity is the weakest due to its absence in explicit curriculum objectives. Teachers’ and students’ perceptions acknowledge the curriculum’s relevance, but its implementation is influenced by teacher competency, facilities, teaching strategies, school culture, technology readiness, material relevance, and managerial support, all of which determine the curriculum’s alignment with 21st-century graduate profiles.